The Influence of Health Education on the Prevention of Anemia and Stunting in Adolescent Girls at SMAN 1 Wawotobi - Islamiyah islamiyah; Asri Dwi Novianti; Leniarti Ali (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction:  Stunting is a chronic nutritional problem with serious long-term impacts. Stunting causes irreversible growth disorders. One of the factors that has the potential to cause stunting is anemia.  This study aimed to determine the effect of health education about anemia and stunting on the knowledge of adolescent girls at SMAN 1 Wawotobi.  Method: This study employed a quantitative study with a cross-sectional design. The sample consisted of 80 female students at SMAN 1 Wawotobi. A questionnaire was administered to assess knowledge before and after health education. The analysis method used the chi-square test to determine the average level of knowledge of respondents after health education. Results: The results showed an increase in knowledge among adolescent girls after health education about anemia and stunting. Conclusions:These results are expected to provide additional references on the importance of preventing stunting as early as possible, especially in adolescent girls, to meet their nutritional needs and prevent anemia, thus producing a stunting-free generation.